2016
DOI: 10.1080/02705060.2016.1231137
|View full text |Cite
|
Sign up to set email alerts
|

Effects of energy development on wetland plants and macroinvertebrate communities in Prairie Pothole Region wetlands

Abstract: Energy production in the Williston Basin, USA, results in the coproduction of highly saline, sodium chloride-dominated water (brine). The Prairie Pothole Region (PPR) overlies the northeastern portion of the Williston Basin. Although PPR wetlands span a range of salinity, the dominant salt is sodium sulfate, and salinities are much lower than brine. Introduction of brine to wetlands can result in pronounced water-quality changes; however, the ecological effects of such contamination are poorly understood. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 13 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…However, numerous other wetland studies have cited the importance of salinity (e.g. Preston & Ray, ), turbidity (Maurer et al., ; Stewart & Downing, ) and phosphorus (McCormick, Shuford, & Rawlik, ; Silver, Thompson, et al., ) in structuring aquatic macroinvertebrate communities. The only relationship to water quality that we detected in our study system was a mild association ( r 2 = .139) between sodium and a variation in community composition along our second ordination axis.…”
Section: Discussionmentioning
confidence: 99%
“…However, numerous other wetland studies have cited the importance of salinity (e.g. Preston & Ray, ), turbidity (Maurer et al., ; Stewart & Downing, ) and phosphorus (McCormick, Shuford, & Rawlik, ; Silver, Thompson, et al., ) in structuring aquatic macroinvertebrate communities. The only relationship to water quality that we detected in our study system was a mild association ( r 2 = .139) between sodium and a variation in community composition along our second ordination axis.…”
Section: Discussionmentioning
confidence: 99%
“…The values reported by Fennessy et al (1994) for Illinois wetlands convert to 44.1 to 375.3 g C/m 2 for emergent plants, 1.80 to 2.70 for floating leaved plants, and 6.30 to 8.10 for submerged aquatic plants. Preston and Ray (2017) measured bulrush biomass values that ranged from 18 to 60 g C/m 2 for prairie potholes. The values for Alabama bulrush convert to 788, 1553, and 2713 g C/m 2 , whereas cattails were 199, 337, and 624 g C/m 2 for June, August, and November, respectively.…”
Section: Resultsmentioning
confidence: 97%
“…For comparison, Fennessy et al (1994) reported biomass values for emergent (49-417 g dry wt/0.5 m 2 ), floating leaved (2-3 g dry wt/0.5 m 2 ), and submerged (7-9 g dry wt/0.5 m 2 ) aquatic plants in low-flow constructed wetlands in Illinois. Preston and Ray (2017) measured bulrush biomass values that ranged from 18 to 60 g C/m 2 for prairie potholes. Behrends et al (1994) reported total dry matter for several species of emergent aquatic plants sampled from wetlands in Alabama.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have identified contamination of wetlands and groundwater resources, including drinking water aquifers, located on U.S. Fish and Wildlife Service, Tribal, and public lands, and numerous groups have expressed concern over the potential risk of contamination (Preston and Ray, 2017;Peterman and others, 2010). Currently, the extent of such contamination across the Williston Basin is unknown, and there is a need for scientificbased information to assess this threat.…”
Section: Bakken Formation/williston Basin Crude Oil Research Needsmentioning
confidence: 99%